(untitled) (Sociologisk Forskning, 2018)
A housewife “at home”. Returning migrant women’s encounters of Swedish gender equality in policy and in practice This article discusses the experiences of Swedish migrant women who are returning to Sweden after having lived abroad for a period of their lives. Most of them have been situated outside the formal labour market during their time abroad and been occupied with family related work. The aim of this article is to analyse how political ideals formulated around work, gender equality and income redistribution, encounter the constructions of Swedishness, gender and heterosexuality in these women’s stories. When living abroad, the women were provided for by their husbands. Yet, their positions as “trailing spouses” had had severe impact on their opportunities for reintegration into the labour market as well as for their future – or current – pensions. The article discusses the political and sociological consequences of women’s economic dependence, primarily in terms of welfare state distribution and pensions by asking: In what ways are returning migrant women situated in-between a global labour market and the Swedish welfare system in relation to migration, gender and gender equality?